2014
DOI: 10.1038/srep06067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soccer shoe upper on ball behaviour in curve kicks

Abstract: New soccer shoes have been developed by considering various concepts related to kicking, such as curving a soccer ball. However, the effects of shoes on ball behaviour remain unclear. In this study, by using a finite element simulation, we investigated the factors that affect ball behaviour immediately after impact in a curve kick. Five experienced male university soccer players performed one curve kick. We developed a finite element model of the foot and ball and evaluated the validity of the model by compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…First, the bone and cartilage of the foot were fused in this study to simplify the model upon considering the complex computational environment of multibody coupling. At present, several studies have shown that it is feasible to use fused bone for research ( Ishii et al, 2014 ; Nouman et al, 2021 ), but there are also studies showing that the use of fused bone will increase the contact pressure. Therefore, the multibody coupling model used here must be refined ( Wang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the bone and cartilage of the foot were fused in this study to simplify the model upon considering the complex computational environment of multibody coupling. At present, several studies have shown that it is feasible to use fused bone for research ( Ishii et al, 2014 ; Nouman et al, 2021 ), but there are also studies showing that the use of fused bone will increase the contact pressure. Therefore, the multibody coupling model used here must be refined ( Wang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this suggests the importance of correctly defining the materials’ properties in certain product areas, such as stitched and perforated ones. In existing studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ], the properties are considered homogeneous over the entire surface of the footwear’s upper.…”
Section: Discussionmentioning
confidence: 99%
“…The regular samples were cut in parallel and perpendicular to the backbone from the shoulder, butt and belly areas. In other studies, the properties of upper assembly are considered homogeneous over the entire surface of the footwear’s upper [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. However, footwear is a structural complex multilayer product, where its parts/components are organised into groups and subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…However, the magnitudes of what is considered too high or too low were not defined. Others have attempted to model the foot to ball interaction, including mathematical models [4] and finite element models [5,6]. Nevertheless, these two approaches require the foot to ball Coefficient of Friction (COF) for any realistic modelling.…”
Section: Introductionmentioning
confidence: 99%